The use of propranolol for complicated infantile hemangiomas. (8th July 2013) - Vercellino, Nadia; Romanini, Maria Victoria; Pelegrini, Monica; Rimini, Alessandro; Occella, Corrado; Dalmonte, Pietro
Abstract Objective To assess propranolol efficacy and safety in complicated infantile hemangiomas in two different age groups. Patients and methods We report on 68 infants with infantile hemangiomas treated with oral propranolol at the lowest effective dose at different ages for a period of six months. Inclusion criteria were life‐threatening hemangiomas, function‐threatening hemangiomas, facial hemangiomas with risk for disfigurement, and extensive and ulcerated hemangiomas. A previously designed safety protocol was applied to all patients. The evolution of all hemangiomas since baseline (pre‐therapy) until the end of follow‐up was assessed on the basis of clinical features (color, palpable softening, size, and volume) and taken at follow‐up visits. Results Our results showed that propranolol was effective in arresting the proliferative phase and in accelerating the involution of infantile hemangiomas in 92.6% of cases. Propranolol efficacy was clear even when it was started after 12 months of life at low dose; after discontinuation of therapy there was a moderate‐to‐severe regrowth in 9.3% of cases and a mild regrowth in 22.5%. No adverse events were observed. Conclusions Propranolol should be used as first‐line medical treatment in all cases of complicated infantile hemangiomas.